An Integrated Model of E-Service Quality, Trust, E-Satisfaction, and E-Loyalty in Digital Commerce - Fatmasari; Andi Irmayana; Nasaruddin; Sitti Mujahida Baharuddin (Global Review of Tourism and Social Sciences, 2026)
This study investigates how Integrated Marketing Communication shapes brand preference through the mediating roles ofBrand Awareness and Brand Image within the ceiling and interior materials industry in Indonesia. Using survey data from 345 consumers and analyzed through Partial Least Squares Structural Equation Modeling, the study demonstrates that Integrated Marketing Communication has significant positive effects on awareness, image, and preference. Brand Awareness and Brand Image also emerge as strong predictors of brand preference, indicating that both familiarity and favourable associations are central to consumer decision making. The results further reveal a sequential mediation pathway in which Integrated Marketing Communication enhances awareness, awareness strengthens image, and image ultimately drives preference. These findings contribute to a deeper understanding of the cognitive and evaluative processes linking communication strategy to consumer choice. The study offers practical insights for firms seeking to build brand equity in competitive markets.